Associations between primary aldosteronism and diabetes, poor bone health, and sleep apnea—what do we know so far? - Loh, Huai Heng; Norlela, Sukor (Springer Nature Limited, 2020)
Primary aldosteronism (PA), the most common cause of secondary hypertension, is a well-recognized condition that can lead to cardiovascular and renal complications. PA is frequently left undiagnosed and untreated, leading to aldosterone-specific morbidity and mortality. In this review we highlight the evidence linking PA with other conditions such as (i) diabetes mellitus, (ii) obstructive sleep apnea, and (iii) bone health, along with clinical implications and proposed underlying mechanisms.